Is early short-term intensive insulin treatment an option to preserve ß-cell function in type 2 diabetes? - Kohnert, K.-D.; Heinke, P.; Vogt, L.; Freyse, E.-J.; Kohnert, L.; Meyramov, G.G.; Salzsieder, E. (Fundamental and Experimental Biology, 2015)
Type 2 diabetes mellitus is a complex metabolic disorder characterized by a relative deficiency of insulin in the presence of hepatic, adipose tissue, and skeletal muscle insulin resistance. The pathological process underlying the ß-cell dysfunction occurs already prior to the disease onset. While at the initial stage, ß-cell mass and insulin secretory function are sufficiently well maintained in the majority of individuals with type 2 diabetes, the later stages are characterized by aggravating insulin deficiency. The clinical course of the disease requires escalating therapy with oral drugs over time and eventually consistent application of insulin at the late stage for control of glycemia. Oral therapies are quite effective in improving the short-term insulin secretory capacity, but are incapable of preventing the inexorable decline in ß-cell function during diabetes progression. On the other hand, long-term use of antidiabetic agents is not without various side effects. Since a series of clinical trials have recently shown that implementation of short-term intensive insulin therapy in in-dividuals with newly diagnosed type 2 diabetes can drastically improve and preserve ß-cell function and induce glycemic remission, this treatment strategy has gained considerable interest. However, whether early intensive treatment with insulin can really provide longer-term protection of the pancreatic ß-cells and may be preferable to other therapy modalities is a question that is not yet clearly established and requires appropriate clinical studies.